Chronology of The Revelation of The Qur'an From The Perspective of Sir William Muir: Its Relevance To The Study Of Modern Tafsir - Rezwandi Rezwandi (An Najah (Jurnal Pendidikan Islam dan Sosial Keagamaan), 2025)
This study examines the theory of the chronological transmission of the Qur'an from the perspective of Sir William Muir, who is considered one of the significant Orientalist constructions that influenced the evolution of contemporary exegesis studies. The main focus of this study is to systematically describe the six stages of the revelation of the Qur'an as presented by Muir, as well as to analyse his role in the formation of the historical-critical approach in tafsir studies. By applying a descriptive qualitative analysis methodology complemented by a historical-comparative review, this research explores Muir's seminal work, The Life of Mahomet and History of Islam. The findings of the study indicate that Sir William Muir categorised the process of the revelation of the Qur'an into six main periods: (1) the pre-prophetic recitation period; (2) the early prophetic period; (3) the period of rebellion and opposition to the Quraish tribe; (4) the period of narratives about the Jews and Arab society; (5) the period of the lifting of the ban approaching the hijrah; and (6) the Madinah period. The relevance of Muir's theory to modern exegesis studies is evident in its influence in shaping the historical-critical approach that places revelation in its chronological, social, and cultural context, thereby helping to open up a more dynamic understanding of the process of revelation and interpretation of the Qur'an. The contribution of this research lies in affirming the relevance of Muir's methodology to the modern interpretation paradigm, namely in encouraging scientific awareness of the importance of reading the Qur'an chronologically and contextually.